2009
DOI: 10.1097/cad.0b013e32832bd1e3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pancreatic cancer by the beta-blocker propranolol

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is among the leading causes of cancer deaths and is unresponsive to existing therapy. Smoking and alcohol-induced pancreatitis are among the risk factors for PDAC. We have previously reported that beta-adrenergic receptors (β-ARs) stimulate the proliferation and migration of human PDAC cells in vitro via cAMP-dependent signaling and that the nicotine-derived nitrosamine NNK activates this pathway directly in vitro while additionally stimulating the release of noradrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 32 publications
3
70
0
Order By: Relevance
“…[91][92][93][94][95][96] Indeed, several studies showed the beneficial effects of administering propanolol as an unselective β-blocker with reduced pancreatic cancer incidence in hamsters with ethanol-induced pancreatitis. 97 At the cellular level, β-adrenergic receptors were shown to stimulate the proliferation and migration of human pancreatic cancer cells by cAMP-dependent signalling. 97 Pancreatic cancer cells are known to upregulate the α7 nicotinic acetyl choline receptor, and this upregulation is associated with induction of phosphorylated cyclic AMP-responsive element-binding protein (p-CREB), phosphorylated extracellular regulated kinase 1/2 (p-ERK1/2; also known as mitogen activated protein kinase 3/1), and epidermal growth factor and vascular endothelial growth factor in pancreatic cancer cells.…”
Section: Nerves As Modulators Of Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…[91][92][93][94][95][96] Indeed, several studies showed the beneficial effects of administering propanolol as an unselective β-blocker with reduced pancreatic cancer incidence in hamsters with ethanol-induced pancreatitis. 97 At the cellular level, β-adrenergic receptors were shown to stimulate the proliferation and migration of human pancreatic cancer cells by cAMP-dependent signalling. 97 Pancreatic cancer cells are known to upregulate the α7 nicotinic acetyl choline receptor, and this upregulation is associated with induction of phosphorylated cyclic AMP-responsive element-binding protein (p-CREB), phosphorylated extracellular regulated kinase 1/2 (p-ERK1/2; also known as mitogen activated protein kinase 3/1), and epidermal growth factor and vascular endothelial growth factor in pancreatic cancer cells.…”
Section: Nerves As Modulators Of Disease Progressionmentioning
confidence: 99%
“…97 At the cellular level, β-adrenergic receptors were shown to stimulate the proliferation and migration of human pancreatic cancer cells by cAMP-dependent signalling. 97 Pancreatic cancer cells are known to upregulate the α7 nicotinic acetyl choline receptor, and this upregulation is associated with induction of phosphorylated cyclic AMP-responsive element-binding protein (p-CREB), phosphorylated extracellular regulated kinase 1/2 (p-ERK1/2; also known as mitogen activated protein kinase 3/1), and epidermal growth factor and vascular endothelial growth factor in pancreatic cancer cells. 97 Considering the increasing number of studies 98-100 that reported the tumorigenic effects of sympathetic nervous system activation, 101 targeting the sympathetic nervous system in cancers seems to hold promise as a potential future adjunct therapy option.…”
Section: Nerves As Modulators Of Disease Progressionmentioning
confidence: 99%
“…During the last years, several studies have reported that autonomic receptors may regulate tumour proliferation and invasion. Previous reports have demonstrated that b-adrenoceptors may contribute substantially to proliferation of different tumours including pancreatic and vascular tumours and melanoma (Al-Wadei et al, 2009;Chisholm et al, 2012;Dal Monte et al, 2013). b-adrenoceptors have also been suggested to constitute the link between chronic stress and the development of acute lymphoblastic leukaemia (ALL) and pancreatic cancer (Lamkin et al, 2012;Kim-Fuchs et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…With regards to pancreas cancer, β-adrenergic agonists stimulate human ductal adenocarcinoma cell growth via adenyl cyclase, which has downstream effects on cAMP, protein kinase A (PKA), and phosphorylation of cyclic AMP response element binding protein (p-CREB) 54,59. PKA also activates the EGFR pathway.…”
Section: β-Blockersmentioning
confidence: 99%
“…PKA also activates the EGFR pathway. Furthermore, tobacco, via the carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), may also stimulate pancreatic cell growth via this same β-adrenergic mechanism 54,60. In an animal model of hamsters with ethanol-induced pancreatitis, the nonselective β-blocker propranalol showed strong antineoplastic effect, inhibiting upregulation of the α7 nicotinic acetylcholine receptor (α7nAChR) as well the extracellular signal regulated protein kinases (ERK1/2), p-CREB, EGF, and vascular endothelial growth factor 54…”
Section: β-Blockersmentioning
confidence: 99%